Pelatihan Kader Olahraga Masyarakat tentang Penyelenggaraan Pertandingan yang Aman dan Sehat (Indonesian Version) - Agus Zainuri; Lily Bauw; Syahruddin Syahruddin; Ansar CS; Ipa Sari Kardi; Muh Syaiful Syam; Marsuki Marsuki (Harmoni Sosial : Jurnal Pengabdian dan Solidaritas Masyarakat, 2025)
The training of Community Sports Cadres on Organizing Safe and Healthy Matches is motivated by the increasing number of sporting events which often ignore safety and health aspects. This activity involved 40 participants from the local community and the South Jayapura district youth organization. The aim of the activity is to increase understanding and skills in organizing matches in accordance with safe and healthy standards. The training method applied includes several steps, namely a pretest to measure participants' initial knowledge, followed by an education and training session that includes theory and practice, then ending with an evaluation. After the session, a posttest was carried out to assess the increase in participants' understanding. The evaluation results showed a significant increase in participants' knowledge; The percentage of participants who understood the material rose from 67% of participants who understood and 33% of participants who did not understand during the pretest to 93% of participants who understood and the remaining 7% who did not understand after education and training. The conclusion of this activity shows that the training succeeded in achieving its goal of increasing the capacity of safe and healthy sports cadres. The resulting suggestion is the need to carry out similar training on a regular basis to continue to educate and empower the public in the safety and health aspects of organizing sports.